2016
DOI: 10.3390/ma9030178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca Content on Formation and Photoluminescence Properties of CaAlSiN3:Eu2+ Phosphor by Combustion Synthesis

Abstract: Effects of Ca content (in the reactant mixture) on the formation and the photoluminescence properties of CaAlSiN3:Eu2+ phosphor (CASIN) were investigated by a combustion synthesis method. Ca, Al, Si, Eu2O3, NaN3, NH4Cl and Si3N4 powders were used as the starting materials and they were mixed and pressed into a compact which was then wrapped up with an igniting agent (i.e., Mg + Fe3O4). The compact was ignited by electrical heating under a N2 pressure of ≤1.0 MPa. By keeping the molar ratios of Al and Si (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Another of the reasons is the morphology of the as-synthesized products transformed. Chung et al [ 2 ] reported that the three major types of morphology were observed for the synthesized products: plate-like crystals, bar-like crystals, and agglomerated fine particles. Among the three types of morphology of CASIN, the bar-like morphology seems to give a stronger emission than the other two.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another of the reasons is the morphology of the as-synthesized products transformed. Chung et al [ 2 ] reported that the three major types of morphology were observed for the synthesized products: plate-like crystals, bar-like crystals, and agglomerated fine particles. Among the three types of morphology of CASIN, the bar-like morphology seems to give a stronger emission than the other two.…”
Section: Resultsmentioning
confidence: 99%
“…After the evacuation, the reactor was backfilled with nitrogen to the desired pressures. The combustion reaction was ignited by heating the top surface of the compact for ~10 s by applying an electrical power of ~1 KW to the heating coil [ 1 , 2 ]. After combustion, the igniting agent was converted to MgO + Fe, which was loosely attached to the interior product.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, M 2 Si 5 N 8 : Eu 2+ (M = Ca, Sr, Ba) phosphors give a broad emission band from 570 to 680 nm due to the 5d−4f parity-allowed transition of Eu 2+ , when excited by blue or near-UV LED chips. This means that M 2 Si 5 N 8 : Eu 2+ (M = Ca, Sr, Ba) is a good candidate for red-emitting phosphor, which can convert the blue or near-UV light of LED chips into red light [11][12][13]. The most common synthesis technique for nitride phosphor is high-temperature reaction, where precursors (Ca 3 N 2 , Sr 3 N 2 and EuN) are very sensitive to air and moisture [1,9,14,15].…”
Section: Introductionmentioning
confidence: 99%